2021
DOI: 10.1155/2021/5529913
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Improves Cardiomyocyte Vulnerability to Hypoxia by Regulating SIRT1/TMBIM6‐Related Mitophagy and Endoplasmic Reticulum Stress

Abstract: Cardiomyocyte apoptosis is an important pathological mechanism underlying cardiovascular diseases and is commonly caused by hypoxia. Moreover, hypoxic injury occurs not only in common cardiovascular diseases but also following various treatments of heart-related conditions. One of the major mechanisms underlying hypoxic injury is oxidative stress. Quercetin has been shown to exert antioxidant stress and vascular protective effects, making it a promising candidate for treating cardiovascular diseases. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 41 publications
(24 reference statements)
0
57
0
Order By: Relevance
“…Moreover, deletion of PINK1 in this context abrogates the beneficial effect of hydrogen, suggesting that over-activation of PINK1/parkin-mediated mitophagy is essential for the anti-apoptotic and anti-inflammatory effect of hydrogen during cardiac I/R [ 95 ]. Furthermore, several studies showed that pharmacological activation of PINK1/parkin-mediated mitophagy is cardioprotective following H/R [ 103 , 104 , 105 ].…”
Section: Role Of Mitophagy During and Following Myocardial Infarction (Mi)mentioning
confidence: 99%
“…Moreover, deletion of PINK1 in this context abrogates the beneficial effect of hydrogen, suggesting that over-activation of PINK1/parkin-mediated mitophagy is essential for the anti-apoptotic and anti-inflammatory effect of hydrogen during cardiac I/R [ 95 ]. Furthermore, several studies showed that pharmacological activation of PINK1/parkin-mediated mitophagy is cardioprotective following H/R [ 103 , 104 , 105 ].…”
Section: Role Of Mitophagy During and Following Myocardial Infarction (Mi)mentioning
confidence: 99%
“…Quercetin is an effective active ingredient extracted from a variety of medicinal plants or Chinese herbal medicines (142,143). It has a good therapeutic effect on cardiovascular diseases.…”
Section: Pharmacological Intervention In Animalsmentioning
confidence: 99%
“…In addition, it plays an important role in cardiomyocyte injury. Ji et al (142) studied the pharmacological effects of quercetin on human cardiomyocytes. The study using hypoxia/reoxygenation(H/R)pretreated human cardiomyocytes showed that H/R induced excessive ROS, leading to mitochondrial energy metabolism disorder and endoplasmic reticulum stress, accompanied by a decrease in mitophagy level, finally leading to the apoptosis of cardiomyocytes and a decrease in human cardiomyocyte activity.…”
Section: Pharmacological Intervention In Human Clinical Trialsmentioning
confidence: 99%
“…Quercetin is a flavonoid that is widely present in nature. Pharmacological studies have reported that quercetin can delay vascular endothelial functional damage and cardiac terminal damage [27]. Quercetin also has a regulatory role in the prevention of myocardial fibrosis [28] and can further regulate islet function.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin also has a regulatory role in the prevention of myocardial fibrosis [28] and can further regulate islet function. Moreover, we previously found that quercetin can regulate mitophagy and endoplasmic reticulum stress through SIRT1/TMBIM6, improve mitochondrial energy metabolism, and protect human cardiac myocytes [27]. However, the regulatory mechanisms underlying the effect of quercetin on SIRT5 succinylation and its protective effect on myocardial cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%